2016
DOI: 10.1902/jop.2016.160013
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators for Periodontitis in US Adults: NHANES 2009 to 2012

Abstract: Assessment of risk profiles for periodontitis in adults in the United States based on gold standard periodontal measures show important differences by severity of disease and sex. Cigarette smoking, specifically current smoking, remains an important modifiable risk for all levels of periodontitis severity. Higher likelihood of TP in older adults and in males with uncontrolled DM is noteworthy. These findings could improve identification of target populations for effective public health interventions to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
175
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(198 citation statements)
references
References 30 publications
15
175
1
7
Order By: Relevance
“…It is well-documented that clinical periodontal parameters among CS and STU have increased percentage of deep probing depths, a higher clinical attachment loss, and increased alveolar bone loss compared with NTU 16,17 ; however, to our information from the literature, the present study is the first study to compare clinical and radiographic parameters around dental implants and proinflammatory cytokine levels among CS (Group-1), STU (Group-2), and NTU (Group-3). The purpose of the present study is supported on the hypothesis that periimplant clinical and radiographic inflammatory parameters are worse in CS and STU compared with nontobacco users.…”
Section: Discussionmentioning
confidence: 80%
“…It is well-documented that clinical periodontal parameters among CS and STU have increased percentage of deep probing depths, a higher clinical attachment loss, and increased alveolar bone loss compared with NTU 16,17 ; however, to our information from the literature, the present study is the first study to compare clinical and radiographic parameters around dental implants and proinflammatory cytokine levels among CS (Group-1), STU (Group-2), and NTU (Group-3). The purpose of the present study is supported on the hypothesis that periimplant clinical and radiographic inflammatory parameters are worse in CS and STU compared with nontobacco users.…”
Section: Discussionmentioning
confidence: 80%
“…24 Eke et al in recent American national studies have observed the differential blurring of differences among sexes in periodontitis prevalence as defined by the CDC/AAP, which has been explained by the postmenopausal condition of women, when estrogen deficiency increases destructive processes within the periodontium. 46 It should be borne in mind that the negative impact of the male gender may result from other factors associated with it, such as more frequent tobacco addiction or considerably worse oral hygiene (confirmed by own studies). The impact of the current tobacco addiction upon the development and clinical course of periodontitis is clear and strong.…”
Section: Discussionmentioning
confidence: 88%
“…This methodology has been proposed in the USA and currently it is used exclusively in epidemiological studies,whereas in Europe it is only now introduced. 16,17,21,24,46 Eke et al have shown that the use of a periodontal examination protocol other than a comprehensive oral examination may lead to underestimating the morbidity of periodontitis even by 50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations